2014
DOI: 10.17221/7499-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of proteins in feeds according to the CNCPS and comparison to in situ parameters

Abstract: Several methods were used for the evaluation of feed protein for rumen degradability and intestinal digestibility of rumen undegraded protein (RUP). The aim of this work was to explore the possibility of using the Cornell method of predicting the fraction RUP. An in situ method was adopted for estimation of degradability parameters (a, b, c) and effective degradable crude protein (EDCP), and five nitrogen fractions (A, B 1 , B 2 , B 3 , and C) were determined according to the Cornell Net Carbohydrate and Prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 16 publications
3
11
3
Order By: Relevance
“…The NPN concentration in cereal grains is relatively low as compared to other feedstuffs (Chrenková et al, 2014;Westreicher-Kristen, Steingass, & Rodehutscord, 2012). Accordingly, only small differences were detected between the sum of the analysed AA and CP concentrations for samples examined in the present study.…”
Section: Estimation Of Utilisable Cp At the Duodenumcontrasting
confidence: 57%
See 1 more Smart Citation
“…The NPN concentration in cereal grains is relatively low as compared to other feedstuffs (Chrenková et al, 2014;Westreicher-Kristen, Steingass, & Rodehutscord, 2012). Accordingly, only small differences were detected between the sum of the analysed AA and CP concentrations for samples examined in the present study.…”
Section: Estimation Of Utilisable Cp At the Duodenumcontrasting
confidence: 57%
“…This fraction could lead to high levels of microbial protein synthesis in vitro, which are washed out during in situ incubations. The NPN concentration in cereal grains is relatively low as compared to other feedstuffs (Chrenková et al., ; Westreicher‐Kristen, Steingass, & Rodehutscord, ). Accordingly, only small differences were detected between the sum of the analysed AA (Rodehutscord et al., ) and CP concentrations for samples examined in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The fraction A for our results of grain meals, rapeseed feeds, pasture forages and silages achieved mean values of 144.9, 206.8, 296.3 and 468.2 g/kg CP, respectively. These findings are in agreement with several authors (Choi et al, 2002;Chrenková et al, 2014;Polat et al, 2014). The same author noted that data on the nitrogen fractions determined according to the CNCPS system of lupine grains were lacking.…”
Section: Resultssupporting
confidence: 92%
“…The high proportions of SolP, A (NPN) in MS n as a result of intensive protein hydrolysis during ensiling. 21 Similar to our study, Sniffen et al, 11 showed that B 1 fraction of forages is very low. Generally, when forages are conserved through ensiling or drying, there is a shift in the proportion of B 1 and B 2 towards A (NPN) in silage and B 3 in dried forages.…”
Section: The Cncps Parameterssupporting
confidence: 91%